PENGARUH PRICE EARNING RATIO, MARKET TO BOOK VALUE DAN OPERATING LEVERAGE TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Fitri Lutfiana, 09.05.51.0080 (Students Journal of Economic and Management, 2013)
Basically every investor that invests so expect to benefit from these investments in the future. The advantage is a compensation for the time and risk associated with the investment in doing. Purpose of investing is to maximize investor return, without forgetting the risk factors they face. Before investing, prospective investors would require information relating to the implementation of the investment. Analysis of financial ratios include leverage and market ratios. Research on the relationship Price Earning Ratio, Market to Book Value and stock returns by Farah Margaretha and Irma Damayanti (2008) which states that the Price Earning Ratio and Amrket to Book Value significantly affect stock returns. And, research on the relationship Operating Leverage for stock returns Medeiros et.al.(2003) showed that the OL has a significant effect on stock returns. This study population is a manufacturing company whose shares are actively traded during 2008 to 2010. Sample selection techniques conducted by purposive sampling to obtain a sample size 79 issuers. Analysis of the data used to answer the research hypotheses used multiple regression analysis tool, having previously tested the normality of the data and the classical assumptions. In addition, this study also tested the fit of the model. Test equipment is conducted by the F test and the coefficient of determination. The results of this study indicate that the Price Earning Ratio has negative and significant impact on Stock Return; Market to Book Value positive but not significant impact on Stock Return, and Operating Leverage had significant effect Stock Return . Keywords: Price Earning Ratio, Market to Book Value, Operating Leverage and Return of Shares